The estimation of the economic efficiency of remote monitoring with uav usage in agrarian sector - Lysenko, V.; Pasichnyk, N.; Komarchuk, D.; Opryshko, O. (Енергетика і автоматика, 2017)
The features remote monitoring of plant nitrogen nutrition using unmanned aerial vehicles. Shown the possibility to use for monitoring the nitrogen the additive color model RGB, including the standard board optical equipment. Modern UAVs are able to quickly receive spectral information about the state of the whole field, as well as its individual parts with appropriate positioning. This makes it possible to use techniques for fertilizing equipment equipped only with positioning equipment, which is fundamentally cheaper than additional touch equipment for leaf diagnostics. Has been made the calculation of economy affectivity of differential inputting fertilize. Has been proposed the use of UAV in crop plants for inputting the fertilizer is possible with the use of agricultural equipment equipped with positioning systems. Delineated for UAV it is expedient to develop vegetation indices adapted exactly for such equipment. Has been shown the possibility of using for monitoring the state of nitrogen nutrition may use red and green components of the visible spectrum, which can be provided at standard optical UAVs equipment.